The Purchase Decision Of Qweenaa Shop Fashion Products Based On Online Promotion Through Social Media And Product Variation (Survey On Qweenaa Shop Tasikmalaya Consumers) - Risma Nurmayanti; Depy Muhamad Pauzy; Dudu Risana (Penerbit Jurnal Indonesia, 2023)
The purpose of this study was to determine the purchasing decision of Qweenaa Shop fashion products based on promotion online through social media and product variations (survey of Qweenaa Shop Tasikmalaya consumers). The research method used is descriptive analysis with a quantitative approach, causal method and survey approach to 100 respondents who are consumers of Qweenaa Shop. The type of data used is primary data and secondary data. The data analysis technique used is multiple linear regression analysis. The results of this test prove that online promotions through social media and product variations have a significant effect both partially and simultaneously on purchasing decisions on fashion products at Qweenaa Shop Tasikmalaya.